2022
DOI: 10.1101/2022.11.11.516072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Male mammalian meiosis and spermiogenesis is critically dependent on the shared functions of the katanins KATNA1 and KATNAL1

Abstract: Katanin microtubule severing enzymes are potent M-phase regulators in oocytes and somatic cells. How the complex, and evolutionarily critical, male mammalian meiotic spindle is sculpted remains unknown. Here, using multiple single and double gene knockout mice, we reveal that the canonical katanin A-subunit, KATNA1, and its close paralogue, KATNAL1, together execute multiple aspects of meiosis. We show KATNA1 and KATNAL1 collectively regulate the male meiotic spindle, cytokinesis and midbody abscission, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The increased sensitivity of the embryonic mitotic divisions to KATNA1 depletion compared to the meiotic divisions may be associated with the transition from an acentriolar spindle in oocytes to a more typical mitotic spindle with centrioles and focused spindle poles by the 8-32 cell stage (Courtois et al, 2012; Gueth-Hallonet et al, 1993; Palacios et al, 1993). This is also consistent with findings in spermatogenesis where centriolar spindles persist and, unlike oocytes, katanin deletion has a major impact on spindle organisation and function (Dunleavy et al, 2022; Dunleavy et al, 2021; O’Donnell et al, 2012). Thus, the increasingly important role of katanin in preimplantation embryos relative to the oocyte may be a manifestation of the transition from an acentriolar to centriolar spindle organisation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The increased sensitivity of the embryonic mitotic divisions to KATNA1 depletion compared to the meiotic divisions may be associated with the transition from an acentriolar spindle in oocytes to a more typical mitotic spindle with centrioles and focused spindle poles by the 8-32 cell stage (Courtois et al, 2012; Gueth-Hallonet et al, 1993; Palacios et al, 1993). This is also consistent with findings in spermatogenesis where centriolar spindles persist and, unlike oocytes, katanin deletion has a major impact on spindle organisation and function (Dunleavy et al, 2022; Dunleavy et al, 2021; O’Donnell et al, 2012). Thus, the increasingly important role of katanin in preimplantation embryos relative to the oocyte may be a manifestation of the transition from an acentriolar to centriolar spindle organisation.…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, there is increased evidence in a number of species that acute depletion of gene products leads to a more enhanced phenotype than genetic deletion in vivo , where compensatory mechanisms may come into play (El-Brolosy and Stainier, 2017; Tautz, 1992). In support of this, functional compensation of the katanin A-subunits has been documented (Dunleavy et al, 2022)…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These include the bipolar spindle and midbody during mitosis and meiosis, the manchette for sperm head shaping, and the axoneme, which forms the architectural core of the sperm tail. Previous research has shown that spermatogenesis is dependent on microtubule severing through other members of the meiotic group of the AAA superfamily, the katanins KATNB1, KATNA1, KATNAL2 (summarised by Dunleavy et al, 2022 preprint). The role of spastin in the development of male germ cells has not yet been directly tested.…”
Section: Introductionmentioning
confidence: 99%